PENGARUH KARAGENAN TERHADAP MUTU SIRUP KESEMEK (Diospyros kaki L.) - Siringoringo, Desli Hernika Sari; Harun, Noviar '; Rossi, Evy ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
This study aims to identify the effect of carrageenan on the quality of persimmon syrup and to get the best treatment that complies with the Indonesian National Standard (SNI) 01-3544:2013. The research was conducted experimentally using a completely randomized design (CRD) which consists of seven treatments and three replications, in order to obtain 21 experimental units. The treatment in this study was C0 (with no addition of carrageenan 0%); C1 (with addition of carrageenan as much as 1% (w/v)); C2 (with addition of carrageenan as much as 1.2% (w/v)); C3 (with addition of carrageenan as much as 1.4% (w/v)); C4 (with addition of carrageenan as much as 1.6% (w/v)); C5 (with addition of carrageenan as much as 1.8% (w/v)) and C6 (with addition of carrageenan as much as 2% (w/v)). The data were analyzed statistically using Analysis of Variance (ANOVA). If the calculated F is greater than or equal to the F table then a further test is conducted using Duncan's New Multi Range Test (DNMRT) at 5% level. The best treatment in this research is the treatment of C3 with the addition of carrageenan of as much as 1.4% (w/v) with no precipitates, viscosity of 1440.70 cP, sucrose of 82.00% and the result of sensory assessment is yellow, thick, aroma persimmon, flavor sweet and favoured by the panelists. Keyword : syrup, persimmon and carrageenan